Effectiveness of the new bobath concept in improving motor function in left hemiparesis after ischemic stroke of the right posterior basal ganglia - Cicilia Febriani Hayuningrum; Dela Fariha Fuadi; Sandra Marvella Winasti; Agus Wiyono (Indonesian Journal of Health Science, 2026)
Stroke is classified into two main types based on its pathophysiology, namely ischemic stroke and hemorrhagic stroke. Ischemic stroke, also known as non-hemorrhagic stroke, occurs due to reduced blood and oxygen to the brain and often results in motor impairments such as hemiparesis, postural control deficits, abnormal gait patterns, and decreased selective movement ability. Damage to the basal ganglia plays a signicant role in movement coordination disorders following stroke. This study aimed to determina the effectiveness of physiotherapy management using the New Bobath Concept in improving postural control, gait patterns, and selective movement ability in a patient with left hemiparesis caused by ischemic stroke unvolving the right posterior basal ganglia. This study employed a case study design. Physiotherapy intervention was conducted using New Bobath Concept over six therapy session within a four-week period. Postural control was assessed using a postural grid, gait pattern changes were analyzed through gait pattern analysis, and selective movement ability was evaluated using the Modofied Motor Assessment Scale (MMAS). The results demostrated improvements in postural control and gait patterns, indicated by a reduction in circumduction during walking. Associative reaction movement began to decrease, although they were still briefly observed during the stance and swing phase. Selective upper extremity movement abiluty also improved, with MMAS scores increasing from 28 at the initial assessment (T1) to 42 at the final assessment (T6). These findings suggest that physiotherapy intervention using New Bobath Concept is effective in improving postural control, enhancing gait patterns, and increasing selective movement ability in patients with hemiparesis following ischemic stroke. The New Bobath Concept can be considered a relevant therapeutic approach in post-stroke rehabilitation to optimize functional recovery.